A Randomized Comparison of Programmed Intermittent Epidural Bolus with Continuous Epidural Infusion for Labor Analgesia - Wong, Cynthia A.; Ratliff, John T.; Sullivan, John T.; Scavone, Barbara M.; Toledo, Paloma; McCarthy, Robert J. (Anesthesia and analgesia, 2006)
Bolus injection through an epidural catheter may result in better distribution of anesthetic solution in the epidural space compared with continuous infusion of the same anesthetic solution. In this randomized, double-blind study we compared total bupivacaine consumption, need for supplemental epidural analgesia, quality of analgesia, and patient satisfaction in women who received programmed intermittent epidural boluses (PIEB) compared with continuous epidural infusion (CEI) for maintenance of labor analgesia. The primary outcome variable was bupivacaine consumption per hour of analgesia. Combined spinal epidural analgesia was initiated in multiparas scheduled for induction of labor with cervical dilation between 2 and 5 cm. Subjects were randomized to PIEB (6-mL bolus every 30 min beginning 45 min after the intrathecal injection) or CEI (12-mL/h infusion beginning 15 min the after the intrathecal injection). The epidural analgesia solution was bupivacaine 0.625 mg/mL and fentanyl 2 μg/mL. Breakthrough pain in both groups was treated initially with patient-controlled epidural analgesia (PCEA) followed by manual bolus rescue analgesia using bupivacaine 0.125%. The median total bupivacaine dose per hour of analgesia was less in the PIEB (n = 63) (10.5 mg/h; 95% confidence interval, 9.5–11.8 mg/h) compared with the CEI group (n = 63) (12.3 mg/h; 95% confidence interval, 10.5–14.0 mg/h) (P < 0.01), fewer manual rescue boluses were required (rate difference 22%, 95% confidence interval of difference 5% to 38%), and satisfaction scores were higher. Labor pain, PCEA requests, and delivered PCEA doses did not differ. PIEB combined with PCEA provided similar analgesia, but with a smaller bupivacaine dose and better patient satisfaction compared with CEI with PCEA for maintenance of epidural labor analgesia.